2002
DOI: 10.1562/0031-8655(2002)0750519pmorso2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Monitoring of Redox State of Respiratory Chain in Single Live Cells¶

Abstract: A method for monitoring respiratory chain (RC) activity in single live cells is described. It is based on the registration of the photothermal (PT) response after a laser pulse of a live single cell. The dependence of the PT‐response amplitude and shape upon redox state of RC components was studied with a PT microscope for two in vitro models: (1) solutions of the RC component cytochrome c and (2) mice hepatocytes. The parameters of the PT responses differed for oxidized and reduced forms of cytochrome c solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Because the nicotine concentration in the blood of passive (or light) smokers ranges from 15 to 100 nM, the new PT assay offers the opportunity to study nicotine's influence at extremely low concentrations for which current analytical techniques are inadequate. In general, the PT assay has many other advantages: imaging of nonfluorescent structure, which applies to the majority of native cells; time-resolved imaging, which allows visualization of nanoscale structures and microbubble dynamics; and compatibility with a standard biologic microscope, although it does not require a time-consuming scanning mode (Lapotko et al, 1996a(Lapotko et al, ,b, 1999(Lapotko et al, , 2002aZharov and Lapotko, 2003a,b). Despite the promising data obtained, additional research is required to evaluate the capability of the PT assay to perform quantitative studies with a focus on mechanism of action and identification of the type of absorbing chromophores as markers of environmental impact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the nicotine concentration in the blood of passive (or light) smokers ranges from 15 to 100 nM, the new PT assay offers the opportunity to study nicotine's influence at extremely low concentrations for which current analytical techniques are inadequate. In general, the PT assay has many other advantages: imaging of nonfluorescent structure, which applies to the majority of native cells; time-resolved imaging, which allows visualization of nanoscale structures and microbubble dynamics; and compatibility with a standard biologic microscope, although it does not require a time-consuming scanning mode (Lapotko et al, 1996a(Lapotko et al, ,b, 1999(Lapotko et al, , 2002aZharov and Lapotko, 2003a,b). Despite the promising data obtained, additional research is required to evaluate the capability of the PT assay to perform quantitative studies with a focus on mechanism of action and identification of the type of absorbing chromophores as markers of environmental impact.…”
Section: Resultsmentioning
confidence: 99%
“…formed by individual cellular chromophores different location, chromophore's clusters, or organelles with absorbing biomolecules). Most likely, the observed effects could be explained by the alteration of mitochondrial properties with dominant absorbing substances, such as cytochromes, including cytochromes c (Maile et al, 1987;Weiss, 1987;Karu, 1999;Boustany et al, 2002;Lapotko et al 2002a;). Indeed, Boustany et al (2002) indicated that under specific chemical impact, mitochondria, starting as elongated organelles, formed smaller, sphere-shaped particles.…”
Section: Discussionmentioning
confidence: 99%
“…We have discovered for studied cells rather general and non-specific character of photo-damage phenomena. Earlier using the LLT method, we have obtained the data on influence of some specific physiological processes on the laser-damage threshold and probabilities of live cells: redox state of respiratory chain for hepatocytes [15], processes of cell death (apoptosis and necrosis) for lymphocytes and lymphoblasts [16], and anti-tumor drugs for some cancer cells [17]. In all these cases, despite varieties in biological processes, the similar changes of cellular physical parameters may occur, at least for parameters that are associated with laser-induced bubbles: concentration of light-absorbing molecules (change of cell volume), light-absorption coefficient (redox state of light-absorbing molecules such as cytochromes), and bubble nucleation conditions (e.g., concentration of diluted gases).…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated the correlation between physiological processes in cells and photo-damage phenomena. But they were obtained for in vitro models that assumed influence of one specific parameter (ion balance [14], redox state [15], level of necrosis or apoptosis [16], and drug [17]). Earlier, we have thoroughly studied an influence of ion transport process on damage thresholds of RBC [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation